Manajemen Inovasi dan Perubahan pada Perguruan Tinggi (Studi Kasus Fakultas Dakwah dan Ilmu Komunikasi IAIN Imam Bonjol Padang) - Nora Zulvianti; Riza Riza (Universitas Islam Negeri Imam Bonjol Padang, 2015)
There is nothing being eternal in this world . Everything is changing constantly. Albert Einstein said that a sure thing is “change”. While Evelyn Waugh stated change is the only evidence of life . Change is a necessity in a human life . Process Theory Managerial changes involve a lot of people realize the need for change . The basic concept is to implement a change management strategies and analyzing a change . Colleges have people who are able to analyze the changes